In vitro conservation of the cultivation of spanish carnation (Dianthus caryophyllus L.) from mineral salts. - Jiménez-Mariña, Liudmila (2015)
The objective of the present study was to determine the effect of the salts concentration described by Murashige and Skoog (MS) in short term in vitro conservation of nodal segments of Spanish Carnation (Dianthus caryophyllus L.). The investigation was developed in the Center of Vegetable Biotechnology Studies (CEBV), in the period 2012- 2013. The treatments consisted on the addition of MS salts (100; 75; 50; 25%) and a control (100% + growing regulators) in medium culture. Decreasing until 25% of salts concentration in culture medium reduced the growing speed, being able to conserve for six months under these conditions A survival and recovery of 91,3% was obtained.